(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This article provides insight into English, as a global language, has spread far and wide across the world, becoming the lingua franca of international communication, business, and culture. This phenomenon has been driven by a combination of social, political, and cultural factors that have facilitated the widespread adoption of English in various regions. In this essay, we will explore the key factors contributing to the spread of English across the globe.